A study on the teaching of Islamic studies through critical pedagogy at two private high schools, Jakarta Indonesia - Edwar, Lissa (Institute of Education, International Islamic University Malaysia, 2012)
This research investigated the implementation of critical pedagogy to encourage students' critical thinking in two private high schools, Jakarta, Indonesia. It examined the teachers' practice of teaching Islamic studies critically in the classroom. The major theory of this study is based on the idea of Paulo Freire on the critical pedagogy in his book, the Pedagogy of The Oppressed. The research was conducted using a self-constructed interview protocols and observation. The respondents were two teachers and ten students from two schools which are a good quality school and an average school. The finding showed that teachers who taught in the good quality school practises critical pedagogy to a certain extent. It was also found that the teacher who has a lot of experience and good academic background was good in teaching, in other word the teacher is active and enjoys classroom's activities. This study has found that students from a good school were critical and active compared to students from the average school. The implication of the study is important to educators in all fields of knowledge, more precisely in the field of Islamic studies as well as those who are concerned in the teaching thinking in education. The recommendation for the future study was suggested to examine a larger sample in national schools.